Templated Growth of Crystalline Mesoporous Materials: From Soft/Hard Templates to Colloidal Templates - Zhang, Lei; Jin, Lei; Liu, Ben; He, Jie (Frontiers in Chemistry, 2019)
ABSTRACT: Mesoporous non-siliceous materials, in particular mesoporous transition metal oxides (m-TMOs), are of interest due to their fascinating electronic, redox and magnetic properties for a wide range of applications in catalysis and energy storage. Control of the porosity (e.g., pore size, wall thickness and surface area) and the crystalline degree (e.g. phase composition, crystallinity and crystal grain size) of m-TMOs are critical for those applications. To crystallize TMOs, high temperature annealing is often needed to remove the amorphous defects and/or tune the compositions of different crystalline phases. This has brought many challenges to surfactant or block copolymer templates used in the process of evaporation-induced-self-assembly to prepare m-TMOs. In this minireview, we summarize the most recent achievements including the findings in our own laboratory on the use of organosilicate-containing colloids for the templated growth of mesoporous materials. We review a few key examples to prepare crystalline mesoporous oxides using different templating methods. The colloidal templating method by which mesoporous nanostructures can be stabilized up to 1000 oC is highlighted. The applications of m-TMOs and meso metal-oxide hybrids synthesized using organosilicate-containing colloidal templates in photocatalysis and high-temperature catalysis are also discussed.